Critical Thinking Profile and Learning Interests of Elementary School Students in Human Digestive System Learning - Khoiro, Luh Himmatul; Suprapto , Nadi; Prahani, Binar Kurnia (Papanda Publisher, 2025)
This study aims to comprehensively describe the profile of critical thinking skills among fifth-grade students at SDN Masangan Wetan in the context of learning about the human digestive system. The research focuses on identifying both internal and external factors that support or hinder the development of critical thinking skills. Using an essay-based assessment grounded in Facione’s framework, which includes interpretation, analysis, inference, and evaluation, the study measured students’ critical thinking abilities. Additionally, interviews with teachers provided insights into the instructional strategies, media usage, and teaching models employed to foster critical thinking. The findings show that students’ critical thinking skills vary across different indicators, with the highest proficiency in interpretation and the lowest in evaluation. Internal factors such as motivation, cognitive ability, and self-efficacy positively influence skill development, while external factors including a supportive learning environment, innovative teaching methods, and diverse educational media also play crucial roles. The study found that integrated, interactive media and student-centered models like Problem-Based Learning and collaborative learning significantly enhance critical thinking. Conversely, conventional teaching practices and limited media use restrict students’ critical thinking growth. Teacher interviews highlighted the importance of practical learning activities and varied instructional materials to engage students actively. These results underscore the necessity for educators to implement multifaceted approaches that address both student-internal and environmental factors to optimize critical thinking development. The study involved a total sample of 35 students, and quantitative data were analyzed using descriptive statistics, with mean scores and standard deviations reported to illustrate proficiency levels across critical thinking indicators. Ultimately, the research contributes valuable evidence for educational stakeholders seeking to improve science education quality through enhanced critical thinking skills, especially in primary education settings. Future studies are recommended to include larger samples and statistical tests such as t-tests or ANOVA to strengthen the generalizability and significance of findings.